Capture and transportation of animals from European Bison Breeding Centre of Prioksko-Terrasnyj Nature Biosphere Reserve (European Bison Conservation Newsletter, 2011)
The paper present some methods of European bison transfer between breeding centers. Author discuss how to determine the size of animal body without direct measurements. The methods of preparing and loading and uploading animal is also presented. European bison are transported separate in wooden cages fitted to their size and this method is working properly for more than 50 years.
Keywords: European bison transport; wooden cages